2015
DOI: 10.1039/c5nr01932j
|View full text |Cite
|
Sign up to set email alerts
|

In vivo targeted magnetic resonance imaging and visualized photodynamic therapy in deep-tissue cancers using folic acid-functionalized superparamagnetic-upconversion nanocomposites

Abstract: Multifunctional nanoprobes used in magnetic resonance imaging (MRI) and photodynamic therapy (PDT) also have potential applications in diagnosis and visualized therapy of cancers, and hence it is important to investigate the active-targeting ability and in vivo reliability of these nanoprobes. In this work, folic acid (FA)-targeted, photosensitizer (PS)-loaded Fe3O4@NaYF4:Yb/Er (FA-NPs-PS) nanocomposites were synthesized for in vivo T2-weighted MRI and visualized PDT of cancers by modeling MCF-7 tumor-bearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 41 publications
1
58
0
Order By: Relevance
“…The researches of UCNPs have shown low toxicity and high biocompatibility in vitro and in vivo , which suggests the clinical use in OS treatment [124127]. Of the various modifications of RE materials, the erbium-doped sodium yttrium fluoride (NaYF4:Er 3+ ) system is the most valuable in UCNP-induced PDT, along with ytterbium- and thulium-doped systems, which commonly use a core-shell structure [128130].…”
Section: Novel Strategies In Pdt Of Osmentioning
confidence: 99%
See 1 more Smart Citation
“…The researches of UCNPs have shown low toxicity and high biocompatibility in vitro and in vivo , which suggests the clinical use in OS treatment [124127]. Of the various modifications of RE materials, the erbium-doped sodium yttrium fluoride (NaYF4:Er 3+ ) system is the most valuable in UCNP-induced PDT, along with ytterbium- and thulium-doped systems, which commonly use a core-shell structure [128130].…”
Section: Novel Strategies In Pdt Of Osmentioning
confidence: 99%
“…Beyond the luminous energy transition, UCNP-linked PSs have shown good imaging performance. Zeng's research showed that tumor tissue exposed to NaYF 4 :Yb/Er-based Fe 3 O 4 NPs as T2-weighted MRI contrast agents was significantly darker in vitro and in vivo and inhibition of MCF-7 and HeLa cells was seen with 980-nm laser irradiation [127]. …”
Section: Novel Strategies In Pdt Of Osmentioning
confidence: 99%
“…Zeng et al have also demonstrated the NIR PDT with folic acid (FA)-functionalized, photosensitizer (PS)-loaded Fe 3 O 4 @NaYF 4 : Yb/Er (FA-NPs-PS) nanocomposites both in vitro and in vivo [78]. The PDT caused viabilities of MCF-7 and Hela cells were first studied in vitro.…”
Section: Inorganic Nanoparticle-based Cancer Therapymentioning
confidence: 99%
“…( a ) The relative tumor volume change in different groups; ( b ) the body weight change of mice in different groups; and ( c ) images of different groups of MCF-7 tumor-bearing mice at the beginning and at the end of 15-day treatments. Reprinted with permission from [78]. …”
Section: Figurementioning
confidence: 99%
“…Thus, the combination of FI and MRI into a single nanostructure can offer robust imaging capabilities with the prospect of improved detection accuracy in clinical diagnosis. [29][30][31] To date, there is no commercial probe available in the market with MRI/FI dual-modal capabilities. In the present study, a multifunctional nanoplatform consist of galactosyl conjugated P 123 (Gal-P 123 )-modified IR783-Fe 3 O 4 (GPC@IR783-Fe 3 O 4 ) NPs was designed for dual-modal fluorescence and MR imaging of tumors.…”
mentioning
confidence: 99%